Implementasi Augmented Reality Snap That Animal Menggunakan Metode MDLC Sebagai Media Pembelajaran - Saputra, I Gede Made Mahardikha; Aziza, Rifda Faticha Alfa (Jurnal Teknologi Informasi dan Pendidikan, 2024)
This research introduces Snap That Animal, an augmented reality (AR) mobile application designed as an innovative educational tool for early childhood education. The study focuses on identifying challenges faced by teachers at Aisyiyah Bustanul Athfal Krajan Kindergarten when using traditional teaching methods to engage young learners. To address these challenges, the application was developed using the Multimedia Development Life Cycle (MDLC) method, incorporating the Vuforia SDK on the Android platform to create interactive 3D animal models activated by markers. This interactive approach aims to enhance student interest and learning outcomes by offering more engaging and accessible educational content. The app underwent thorough testing, including marker recognition under varying light intensities, tilt angles, and distances, as well as compatibility with different devices. Results demonstrated that the application performs efficiently in real-life educational settings. A quantitative descriptive approach was employed, with data collected through a questionnaire. The study population consisted of kindergarten teachers, and a total sample of nine teachers participated as respondents. The processed questionnaire results, evaluated using an assessment scale, revealed a feasibility rating of “very good,” with a score of 93.56%. In conclusion, the findings suggest that AR applications like Snap That Animal significantly enhance student engagement and learning effectiveness in early childhood education.